PERAN KESADARAN MEREK MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP EKUITAS MEREK PADA PELANGGAN JASA KURIR JNE - Wulandari, Ida Ayu Laksmi; Rastini, Ni Made (E-Jurnal Manajemen, 2022)
Brand equity is a set of brand assets and liabilities associated with a brand, its name and symbol, which increase or decrease the value provided by a product or service to the company and or the company's customers. This study was conducted with the aim of explaining the effect of service quality on brand equity mediated by brand awareness variables on customers of courier services PT. TIKI Jalur Nugraha Ekakurir (JNE) in Denpasar City. Quantitative research with data collection using questionnaires via google form was carried out on customers of courier services PT. TIKI Jalur Nugraha Ekakurir (JNE) in Denpasar City, with a research sample of 100 people. Technical analysis used is descriptive analysis technique and inferential analysis technique. The results show that service quality has a positive and significant effect on brand awareness, then brand awareness has a positive and significant effect on brand equity, then service quality has a positive and significant effect on brand equity, and brand awareness mediates the effect of service quality on brand equity positively and significantly courier services of PT. TIKI Jalur Nugraha Ekakurir (JNE) in Denpasar City. Keywords: Brand Equity, Brand Awareness, Service Quality.